Evaluasi Penempatan Lokasi Pos Pemadam Kebakaran di Kota Semarang - Cholifatunisa, Diah Hafidha; , Agus Anggoro Sigit, S.Si., M.Sc (2017)
Fire is a disaster that causes environmental damage, loss of property, and psychological impact. The right placement of fire station will minimize the losses caused by the fire. This study aimed to evaluate the location of the fire station and determine the direction of the fire station. The method was used in this study is census and quantitative analysis using a Tiered Approach of Geographic Information System. The parameters were used in this study are the population density, fire-prone areas, the range of services and the existing fire station. The results showed that the fire extinguisher of Genuk sub district and fire station of Pedurungan sub district have alow conformity, mean while in Banyumanik and Tugu sub districts havea moderate conformity, and in West and East of Semarang and Gunungpati have a high conformity. Tutorial placement of the new fire station is located in Candisari sub district with 1 station, Mijen with 2 stations, North Semarang with 1 station,and Ngaliyan with 1 station.